THE USE OF THE FURFURAL FROM THE SOLID WASTE OF SUGAR INDUSTRY (BAGASSE) TO SYNTHESIZE β-(2-FURYL) ACRYLIC ACID AS AN ALTERNATIVE FOR THE RAW MATERIAL OF SUNSCREEN COMPOUND - Mitarlis Mitarlis; Prima Retno Wikandari (Indonesian Journal of Chemistry, 2005)
The research of the usefullness of furfural from bagasse for the production of β-(2-furyl)-acrilyc acid as an alternative raw material of sunscreen compound had been done. The research was done on two stages, the first stage was synthesis of furfural from bagasse and the second was synthesis of β-(2-furyl)-acrilyc acid that is an analog of cynnamic acid in which some derivatives are known possess activities as sunscreen. Cynnamic acid could be produced from benzaldehyde by Perkin methods using alkali hydrolysis. With the similarity of the main structure, so β-(2-furyl)-acrilyc acid can also be synthesized from furfural by Perkin method. The β-(2-furyl)-acrilyc acid had been synthesized in this research from furfural isolated from bagasse by NaOH hydrolysis. Synthesis was done by reflux for 2 hr at 140 - 145 oC and 3 hr at 145 - 150 oC. From the spectroscopic data its known that furfural could be produced from bagasse in 11.65 % yield and 33.83% of β-(2-furyl)-acrilyc acid from the synthesis on the second process. The UV -Vis spectrophotometer analysis result of β-(2-furyl)-acrilyc acids showed λmax at 296.20 nm. It showed that until this step the sunscreen compound can be resulted from furfural isolated from bagasse, especially as a sunscreen that protected skin from eritema (λmax at 290 - 320 nm) that is called as sunscreen UV-B.